Antioxidant, antimicrobial, anti-urease and cytotoxic activities of various extracts from Scutellaria sibthorpii endemic to Cyprus - TAŞKIN, TURGUT (My University, 2022)
Lamiaceae is one of the largest families in the plant kingdom. Including the genus Scutellaria whose species are used in traditional medicine in various countries for prevention and also the treatment of several disorders. In vitro biological activities of the various extracts of the aerial parts from Scutellaria sibthorpii were investigated in the present study. Antioxidant activity of the extracts was measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH), ABTS assays and ferric reducing antioxidant power (FRAP) assays. Cytotoxic potential and anti-urease activities of the extracts were also determined. Spectrophotometric analysis was used to establish the total phenol content of the extracts. The antibacterial activities of extracts were assessed by minimal inhibitory concentration (MIC) against seven bacteria and Candida albicans. Regarding the results, infusion showed considerable antioxidant properties in three method (IC50 value 0.133 +/- 0.0005(DPPH), 26.54 +/- 0.05 mM trolox/mg extract(ABTS), 8.76 +/- 0.1 mM Fe+2/mg extract (FRAP)). Other extracts exhibited high-to-moderate antioxidant effects. Among the studied samples, the infusion had the highest total phenolic content (0.0295 +/- 0.0002 mg GAE/mg extract). According to cytotoxicity results, n-hexane extract had strong cytotoxic effects against PC-3 and NIH/3T3 cell line with IC50 values of 330.40 mu g/mL and 340.85 mu g/mL, respectively. In the antibacterial activity screening, the ethyl acetate extract showed higher activity against Enterecocus facecalis, Klebsiella pneumoniae, Proteus mirabilis with 625 mu g/mL MIC value. According to the research carried out, it would seem that this is the first study on screening biological activities of extracts from Scutellaria sibthorpii. These findings indicate that these endemic species from Cyprus could be used in phytopharmaceutical preparation.
Keywords: Tarımsal Bilimler; Ziraat; Bitki Koruma; Fitopatoloji; Agricultural Sciences; Agriculture; Plant Protection; Phytopathology; BİTKİ BİLİMLERİ; Bitki ve Hayvan Bilimleri; Tarım ve Çevre Bilimleri (AGE); PLANT SCIENCES; PLANT & ANIMAL SCIENCE; Agriculture & Environment Sciences (AGE); Küçük hayvanlar; Bitki Bilimi; Sağlık Bilimleri; Yaşam Bilimleri; Small Animals; Plant Science; Health Sciences; Life Sciences; Antimicrobial; Antioxidant; Anti-urease; Cytotoxic activity; Scutellaria; Traditional medicine; PHENOLIC COMPOSITION; ESSENTIAL OIL; BARBATA; TAXA; BAICALENSIS; INHIBITION